Pengaruh Financial Distress dan Debt Default pada Opini Audit Going Concern - Dewi, Dewa Ayu Nyoman Stari; Latrini, Made Yenni (E-Jurnal Akuntansi; Vol 22 No 2 (2018)DO - 10.24843/EJA.2018.v22.i02.p15, 2018)
Going concern audit opinion is an audit opinion to evaluate entity’s ability in maintaining the entity’s going concern. The aim of this research is to an earn empirical evidence in regard to the effect of the financial distress and debt default on going concern audit opinion . The population on this research was conducted on companies listed in the Indonesian Stock Exchange in the period 2012-2016. Sample chosen by non-probability sampling method with purposive sampling technique. The samples in this research were 190 financial statements data observations, which consist of 38 listed manufactured companies in the Indonesian Stock Exchange in period 2012-2016. The analysis technique used was logistic regression. Based on the results , it can be concluded that financial distress has negative effect on going concern audit opinion and debt default has positive effect on going concern audit opinion. Keywords: financial distress, debt default, and going concern audit opinion.